Study of Rogi Kalyan samitis in strengthening health systems under national rural health mission, district Pune, Maharashtra - Neha Adsul; Manoj Kar (Wolters Kluwer Medknow Publications, 2013)
Background: With objective of health systems strengthening, as visualized under National Rural Health Mission (NRHM); one key strategic intervention is up-gradation of health service delivery facilities so as to provide sustainable quality care with accountability and people's participation, which required the development of a proper management structure called Rogi Kalyan Samitis (RKS). It is the State's attempt to make health everyone's business by de-mystifying health-care delivery at district and sub-district levels with reference to facility based health-care delivery by encouraging citizen's participation in management bodies. Objective: The study was an attempt to define 'functional Health Systems' with a focus on strategic issues concerning RKS operations. Materials and Methods: A mixed-method, multi-site, collective case study approach was adopted. In-depth interviews of key-stakeholders were conducted. Qualitative data were analyzed thematically and coded inductively. Results: RKS is yet to bring out quality component to the health services being provided through facilities. This can be attributed to structural and managerial weakness in the system; however, certainly NRHM has been consistent in creating a road-map for benefitting local community and their participation through RKS. Conclusion: The progress of the RKS can further be enhanced by giving due priority to critical areas. Furthermore, the results emphasize an urgent need for devising strategies and actions to overcome significant systemic constraints as highlighted in the present study.